Highly resolved large eddy simulations of a binary mixture flow in a cavity with two vents: Influence of the computational domain. (2nd April 2019) - Saikali, E.; Bernard-Michel, G.; Sergent, A.; Tenaud, C.; Salem, R.
Abstract: In this article, numerical results from a highly resolved large eddy simulations (LES) of an air-helium buoyant jet developing in a two vented cavity are presented. The simulated configuration mimics the helium-release experiment carried out at CEA Saclay in the framework of security assessment of indoor used hydrogen-based systems. The height of the enclosure was chosen so that a laminar-turbulent transition occurs approximately at the middle of the upstream direction. An exterior region, of different spatial dimensions, has been modeled in the computational domain in order to move the boundary conditions away from the vent surface and to approach the natural inlet/outlet conditions. A sensitivity analysis regarding the size of the exterior region is presented to define the minimum horizontal extension so that the flow inside the cavity is not furthermore influenced by bigger computational domains. We observe mainly that applying an ambient equilibrium-hydrostatic pressure outlet condition directly on the surface of the vent reduces the volume of the air inflow, and thus predicts larger helium mass inside the cavity, in contrary with the cases where an exterior region is considered. A qualification analysis shows that the sub-grid scale model plays a small role in the calculations and thus implies that the LES predictions approach the direct numerical simulation (DNS) solution. Analysis carried out on the time-averaged helium field depicts a concentration regime that is not classical in such configurations and thus the theoretical model used in safety pre-calculations can not be served. Highlights: Modelling an exterior region in the computational domain influences significantly the flow. Global quantities, like volumetric flow rates and fluid mass, are mainly influenced by the computational domain. A sensitive study of the size of the exterior domain is required to provide numerical reference solutions. A concentration regime not situated in the framework of the theoretical model of Linden et al. 1990 is predicted.